2016
DOI: 10.3126/njog.v10i2.14329
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptives Knowledge and Use among Reproductive Aged Women from Squatters of Kathmandu, Nepal

Abstract: Aims: This study aimed to assess the knowledge and use of contraceptives and the associated factors among the married reproductive aged women residing in squatters of Kathmandu, Nepal. Results: A total of 80.7% had knowledge and 66.6% of women were currently using at least one modern contraceptive method. Injectable was most commonly used (58%) whereas condom was the least (3% 0HWKRGV Conclusions:This study showed the actual use of contraceptives was lower than the knowledge. Among the contraceptives XVHG FRQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…And small percentage of them had average score. These results disagree with Devkota, et al [31] who studied "Awareness on cervical cancer among reproductive aged women of Kathmandu, Nepal." concluded that more than two thirds of studied women had average awareness of cervical cancer, 17.9% had good awareness and 11% had poor awareness.…”
Section: Discussioncontrasting
confidence: 80%
“…And small percentage of them had average score. These results disagree with Devkota, et al [31] who studied "Awareness on cervical cancer among reproductive aged women of Kathmandu, Nepal." concluded that more than two thirds of studied women had average awareness of cervical cancer, 17.9% had good awareness and 11% had poor awareness.…”
Section: Discussioncontrasting
confidence: 80%
“…Among those who have had tried alcohol, 38% were using it regularly (1-5 days in 30 days) and 10% classified as daily users (20+ days in a month). Men drink more than women (21 % female as compared to 50% male having taken any type of beverage in the last 30 days)(11) The consumption of alcohol per person among 15 years and older in Nepal for the year 2008-2010 stands at 2.2 (in liters of pure alcohol)which is lower than that for the WHO South-East Asia Region which was 3.5 for the same year. The vast proportion of alcohol that is consumed is made up of unrecorded alcohol (homemade liquor)(3).Like in many other parts of the world alcohol is widely available for sale in the country, in addition the production of homemade liquor for domestic use is allowed by the Liquor Control Act of Nepal.…”
mentioning
confidence: 89%